Junk day - Sellings, Arthur, 1921- (Dobson Science fiction)
Summary: Junk Day London in ruins, millions killed-is this the end for mankind, or a second chance? An unspecified catastrophe has befallen the Earth and civilization lies in ruins. In what remains of London, bands of survivors pick over the detritus of a vanished world, trying to scrape a living from the carcase of thousands of years of mans' achievement, seeking the useful, the edible or that with which they can defend themselves. A new order is emerging, with the nascent society brutally guided by superior force-by the threat of violence and the barrel of a gun. Into this world comes a loner, an artist with a vision all his own and a belief that a civilized world can only emerge from co-operation and culture. In this contest for the future will belief in the essential goodness of mankind win the day? Or will brutality rule? ". . . . his finest novel was his last, Junk Day, a post-holocaust tale set in the ruins of his native London and peopled with engrossing character types . . . . perhaps grimmer than his previous work but pointedly more energetic.